2016
DOI: 10.1371/journal.pone.0148877
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Glutaminase Free Asparaginase from Enterobacter cloacae: In-Vitro Evaluation of Cytotoxic Potential against Human Myeloid Leukemia HL-60 Cells

Abstract: Asparaginase is an important antileukemic agent extensively used worldwide but the intrinsic glutaminase activity of this enzymatic drug is responsible for serious life threatening side effects. Hence, glutaminase free asparaginase is much needed for upgradation of therapeutic index of asparaginase therapy. In the present study, glutaminase free asparaginase produced from Enterobacter cloacae was purified to apparent homogeneity. The purified enzyme was found to be homodimer of approximately 106 kDa with monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 59 publications
1
46
0
2
Order By: Relevance
“…This frequently results in dreadful side effects in patients including a drastic drop in cell counts (WBC and RBC) and severe anemic conditions. Although erythrocytes are not good models for normal cells, to understand whether asparaginase is hemocompatible, hemolysis assay was performed on erythrocytes .The in vitro hemolysis assay results were in concordance with earlier reports of Husain et al and Mahajan et al which showed l ‐asparaginase purified from Enterobacter cloacae and Bacillus licheniformis RAM‐8 was not toxic to human erythrocytes at higher concentrations. This result may suggest that l ‐asparaginase may exert selective cytotoxicity only on leukemic cells, making it an ideal candidate for cancer chemotherapy especially for leukemia.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This frequently results in dreadful side effects in patients including a drastic drop in cell counts (WBC and RBC) and severe anemic conditions. Although erythrocytes are not good models for normal cells, to understand whether asparaginase is hemocompatible, hemolysis assay was performed on erythrocytes .The in vitro hemolysis assay results were in concordance with earlier reports of Husain et al and Mahajan et al which showed l ‐asparaginase purified from Enterobacter cloacae and Bacillus licheniformis RAM‐8 was not toxic to human erythrocytes at higher concentrations. This result may suggest that l ‐asparaginase may exert selective cytotoxicity only on leukemic cells, making it an ideal candidate for cancer chemotherapy especially for leukemia.…”
Section: Discussionsupporting
confidence: 85%
“…The DNA fragmentation results were in concordance with earlier reports by Story et al which showed characteristic fragmentation of DNA of mouse lymphoma cell line (LY‐TH) after l ‐asparaginase treatment indicating apoptosis as the mode of cell death. l ‐asparaginase purified from Enterobacter cloacae also showed characteristic laddering pattern of DNA of human myeloid leukemia HL‐60 cell line . The fragmentation of DNA may be due to the activation of caspase 3 which inactivates DFF‐45 (DNA fragmentation factor) and ICDA (Inhibitor of caspase‐activated DNase) which in turn release active DFF‐40 or CAD (caspase‐activated DNase) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing the presence of glutaminase activity in L-asparaginase preparation will increase the efficacy of ALL treatment. Husain et al (2016), reported the cytotoxicity of purified glutaminasefree asparaginase from Enterobacter cloacae. The purified asparaginase free of glutaminase suppresses the proliferation of cancer cell HL-60 and non-toxic to normal cells in vitro.…”
Section: Isolation and 16s Rrna Analysismentioning
confidence: 99%
“…In addition, most L‐asparaginases have low catalytic activity and low stability as well as are only active in a narrow pH range (Jr et al, ; Zuo, Zhang, Jiang, & Mu, ). Many enzymes with L‐asparaginase activity are quite specific for L‐asparagine, but also have a low level of intrinsic L‐glutaminase activity that hydrolyzes the amino acid L‐glutamine, which is an undesirable effect for the food industry (Husain, Sharma, Kumar, & Malik, ; Shrivastava et al, ). Hence, it is necessary to search for novel L‐asparaginases since drawbacks in the food industry are increasingly reported (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%